More Weapons than Windmills: Japan’s Military and Energy Policy Response to Russia’s Attack on Ukraine - ULV HANSSEN (Czech Journal of International Relations, 2023)
Russia’s attack on Ukraine was a shock to both the international security architecture and global energy markets. This article examines Japan’s response to these shocks. It finds that the Ukraine War spurred dramatic policy changes in Japan’s defense policy, but only moderate ones in its energy policy. The war has so far had a particularly weak impact on Japan’s green transition despite the potential renewable energy has for Japanese energy security. We argue that the main reason for the discrepancy between Japan’s responses in the defense field and energy field is found in its increasingly strong tendency to securitize “the China threat”. Strengthening Japan’s defense policy as a response to Russia’s aggression is seen by Japanese policymakers as compatible with counterbalancing China. However, a full-blown transition to renewable energy is not, due to the Japanese fear of becoming further trade-dependent on China, which dominates renewable energy markets.